The Modern Hearing Care Landscape: Toward the Provision of Personalized, Dynamic, and Adaptive Care - Glista, Danielle; Schnittker, Jean Anne; Brice, Sophie (Seminars in Hearing, 2023)
New technologies and developments in hearing healthcare are rapidly transforming service models, delivery channels, and available solutions. These advances are reshaping the ways in which care is provided, leading to greater personalization, service efficiencies, and improved access to care, to name a few benefits. Connected hearing care is one model with the potential to embrace this “customized” hearing experience by forging a hybrid of health–technology connections, as well as traditional face-to-face interactions between clients, providers, and persons integral to the care journey. This article will discuss the many components of connected care, encompassing variations of traditional and teleaudiology-focused services, clinic-based and direct-to-consumer channels, in addition to the varying levels of engagement and readiness defining the touch points for clients to access a continuum of connected hearing care. The emerging hearing healthcare system is one that is dynamic and adaptive, allowing for personalized care, but also shifting the focus to the client's needs and preferences. This shift in the care model, largely driven by innovation and the growing opportunities for clients to engage with hearing technology, brings forth new, exciting, and sometimes uncomfortable discussion points for both the provider and client. The modern hearing care landscape benefits clients to better meet their needs and preferences in a more personalized style, and providers to better support and address those needs and preferences.
Keywords: connected hearing care; audiology; teleaudiology; person-centered